Vegetation Growth Models Improve Surface Layer Flux Simulations of a Temperate Grassland. Issue 13 (18th January 2018) - Klein, Christian; Biernath, Christian; Heinlein, Florian; Thieme, Christoph; Gilgen, Anna Katarina; Zeeman, Matthias; Priesack, Eckart
Abstract : Core Ideas: Detailed description of plant growth dynamics improves heat flux simulations. Harvest cannot be neglected to adequately simulate boundary layer energy fluxes. Complex plant growth models improve flux exchanges under drought conditions. Grassland models represent interactions of plant growth with soil and agricultural management based on underlying processes in different degrees of detail. To better understand the impact of these differences on the simulation of energy and matter exchange at the land‐surface layer, we compared the ability of five land‐surface models with different degrees of complexity to simulate energy fluxes in an intensively managed grassland in Switzerland. The aim was to evaluate the impacts of biomass growth, biomass harvest, soil profile characterization, and rooting depth on the dynamics of simulated near‐surface soil moisture contents and energy fluxes. The case study included a comparison of model results with continuous observations of latent heat, sensible heat, and net radiation for a site‐year. Energy fluxes were simulated more accurately by including a biomass growth model, encompassing the abrupt decline in leaf area caused by harvest. Site‐specific soil parametrization in combination with the absence of restrictions on rooting depth also improved the simulation results. The simulated energy fluxes of the five models differed significantly in the hot, dry month of July 2010 but were negligible under moist conditions in May. We conclude that the application of dynamic vegetation growth models improves energy flux simulations at the field scale in intensively managed grasslands during summer if biomass harvest dates and site‐specific soil profile descriptions are considered. Our results imply that regional‐scale simulations of grasslands will benefit significantly from high‐resolution input information on soil properties, land use, and management.